Avaliação da sustentabilidade em agroecossistemas hortícolas, com base de produção na agroecologia e na agricultura familiar, na microrregião de Pato Branco – PR - Pasqualotto, Nayara (2013)
Nowadays there is a growing desire from society in relation to some practices that do not damage the environment so intensely. The search for a healthy diet, products with fair prices, social, economic and environmental development permeate the discussions concerning to sustainable development. In this perspective, the theme of this research is the evaluation of the sustainability in horticultural agro systems based its production on Agro ecology and on family farming. It was developed in six agro ecosystems located in the city of Pato Branco – PR. The method to achieve the success of this research was based on the proposal called in Portuguese as which meaning in English is Evaluation of the Management System of Natural Resources Incorporating Sustainability Indicators - MESMIS was accomplished in an active and interdisciplinary way. It was necessary to develop this work build six Sustainability Compounds Indicators: water resources, ground quality, quality of life, economic situation, vegetable and animal diversity and work. These indicators were determined through semi-structured interviews, questionnaires, laboratorial analysis and field observation, in other words, with qualitative and quantitative observation. Based on the conceptions about sustainability developed from the theoretical references and on the familiar farmers perception, as well as the construction of radial graphs, it was possible evaluate the sustainability levels of the agro ecosystems in an integrated way which revealed that the six agro ecosystems maintain the general sustainability indexes between regular and desirable.